STABLE CARBON ISOTOPE FRACTIONATION OF TRANS-1,2-DICHLOROETHYLENE DURING CO-METABOLIC DEGRADATION BY METHANOTROPHIC BACTERIA - Brungard K.L.; Mandernack K.W.; Munakata-Marr J.; Johnson C.A. (My University, 2003)
Changes in the carbon isotope ratio (δ13C) of trans-1,2-dichloroethylene (t-DCE) were measured during its co-metabolic degradation by Methylomonas methanica, a type I methanotroph, and Methylosinus trichosporium OB3b, a type II methanotroph. In closed-vessel incubation experiments with each bacterium, the residual t-DCE became progressively enriched in 13C, indicating isotopic fractionation. From these experiments, the biological fractionation during t-DCE co-metabolism, expressed as ε, was measured to be −3.5‰ for the type I culture and −6.7‰ for the type II culture. This fractionation effect and subsequent enrichment in the δ13C of the residual t-DCE can thus be applied to determine the extent of biodegradation of DCE by these organisms. Based on these results, isotopic fractionation clearly warrants further study, as measured changes in the δ13C values of chlorinated solvents could ultimately be used to monitor the extent of biodegradation in laboratory or field settings where co-metabolism by methanotrophs occurs.